Comparison of the Analgesic Duration of 0.5% Bupivacaine With 1:200, 000 Epinephrine Versus 0.5% Ropivacaine Versus 1% Ropivacaine for Low-Volume Ultrasound-Guided Interscalene Brachial Plexus Block: A Randomized Controlled Trial. (15th January 2021) - Safa, Ben; Flynn, Brendan; McHardy, Paul G.; Kiss, Alex; Haslam, Lynn; Henry, Patrick D.; Kaustov, Lilia; Choi, Stephen
Abstract : BACKGROUND: Bupivacaine and ropivacaine are the preferred long-acting local anesthetics for peripheral nerve blocks as they provide prolonged analgesia in the postoperative period. No studies have directly compared the analgesic duration of these commonly used local anesthetics in the setting of low-volume ultrasound-guided interscalene block (US-ISB). This study was designed to determine which local anesthetic and concentration provides superior analgesia (duration and quality) for low-volume US-ISB. METHODS: Sixty eligible patients scheduled for arthroscopic shoulder surgery were randomized (1:1:1) to receive US-ISB (5 mL) with 0.5% bupivacaine with 1:200, 000 epinephrine, 0.5% ropivacaine, or 1% ropivacaine. All individuals were blinded including study participants, anesthesiologists, surgeons, research personnel, and statistician. All participants received a standardized general anesthetic and multimodal analgesia. The primary outcome was duration of analgesia defined as the time from the end of injection to the time that the patients reported a significant increase in pain (>3 numeric rating scale [NRS]) at the surgical site. RESULTS: The mean duration of analgesia for 0.5% bupivacaine with 1:200, 000 epinephrine, 0.5% ropivacaine, or 1% ropivacaine was 14.1 ± 7.4, 13.8 ± 4.5, and 15.8 ± 6.3 hours, respectively (analysis of variance [ANOVA], P = .51). There were no observed differences in analgesic duration or other secondary outcomes between the 3 groups with the exception of a difference in cumulative opioid consumption up to 20h00 on the day of surgery in favor of ropivacaine 0.5% over bupivacaine of minimal clinical significance. CONCLUSIONS: In the context of single-injection low-volume US-ISB, we have demonstrated a similar efficacy between equal concentrations of ropivacaine and bupivacaine. In addition, increasing the concentration of ropivacaine from 0.5% to 1% did not prolong the duration of US-ISB.